Economic uncertainty and structural reforms - Alessandra Bonfiglioli; Gino Alessandro Gancia (Queen Mary University of London, School of Economics and Finance, 2018)
Does economic uncertainty promote the implementation of structural reforms? We answer this question using one of the most exhaustive cross-country panel data set on reforms in six major areas and measuring economic uncertainty with stock market volatility. To address endogeneity concerns, we propose various identification strategies, instrumenting uncertainty with world shocks to volatility and with natural disasters, political coups and revolutions. Across all specifications, we find that uncertainty has a positive and significant effect on the adoption of reforms. This result is robust to the inclusion of a large number of controls, such as political variables, economic variables, crisis indicators, and a host of country, reform and time fixed effects.
Keywords: E02; E60; L51; 330; Reforms; Uncertainty